STRATEGI PEMASARAN USAHA MIKRO, KECIL, MENENGAH (UMKM) BATIK PEKALONGAN - Hendra Saputra; Dhito Alfeisha (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Micro, small and medium businesses are one of the most important businesses in the national economy. Currently, MSMEs are being intensively implemented in several regions in Indonesia. One of the areas that initiated this business is Batik Pekalongan; There are several educated MSMEs there, one of which is the Batik industry. Any thoughts on the current research question, namely How Do Pekalongan Batik MSMEs Use Marketing Strategies to Increase Usage? The aim of this research is to understand the marketing strategies used by Pekalongan MSMEs to strengthen their businesses. It is hoped that this research will have theoretical and practical benefits that can help in developing marketing strategies to develop business. In this research, qualitative descriptive research was used, where the field observation method used purposive area methodology. In this case, this research uses purposive sampling in the process.